Documented skeletal collections and their importance in forensic anthropology in the United States - Campanacho, Vanessa; Alves-Cardoso, Francisca; Ubelaker, Douglas H. (MDPI, 2021)
Documented skeletal collections are the backbone of forensic anthropology due to their associated biohistories. This paper describes the identified skeletal collections and their relevance in forensic anthropological research, education and training in the US. The establishment of documented skeletal collections in the US can be distinguished into two modus operandi, depending on the stance towards the dead, legislation, and medical and forensic practices. In the 19th and early 20th centuries, anatomists amassed skeletons from cadaver dissections, shaped by European influences. Those skeletons compose the anatomical collections—such as the Robert J. Terry Anatomical Collection—predominantly representing impoverished and unclaimed individuals. Ethical concerns for the curation and research of African American skeletons without family consent are growing in the US. In contrast, since the 1980s, modern documented skeletal collections originated from body donations to human taphonomy facilities, such as the William M. Bass Donated Skeletal Collection. The establishment and testing of osteological methods essential to establish one’s identity—such as age at death and sex—have been developed with skeletons from documented collections. Therefore, the analysis of identified skeletons has been crucial for the development of forensic anthropology in the US.
Keywords: human osteological collections; identified skeletal collections; biographical data; ethics; anatomical collections; human taphonomy facilities; unclaimed cadavers; body donations; biological profile; osteobiographies